Research of the preliminary deformation and irradiation effect on the viscous damping of dislocations in LiF crystals - Petchenko, G.A. (Functional Materials, 2013)
Pulse-echo method in the frequency range of 37.5—232.5 MHz in LiF crystals at T=300 K has been used to study the behaviour of dislocation decrement Δd(f) at variations of the residual strain value and X-ray radiation in the range of 0—400 R. It has been found out that with the increasing doses of radiation the effect of amplitude damping of the dislocation resonance can be observed which leads to a marked restoration of initial acoustic characteristics of the crystals. It has been discovered that the effective length of the dislocation segment L decreases monotonically, while the coefficient of the dynamic viscosity B retains its value at increasing the crystals irradiation dose. The experimental results have been discussed in the framework of existing theories.